2006
DOI: 10.1111/j.1744-7348.2006.00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical response of potato (Solanum tuberosum L. cv. Kara) to O3 and antioxidant chemicals: possible roles of antioxidant enzymes

Abstract: An Egyptian cultivar of potato (Solanum tuberosum L. cv. Kara) was grown in the field at two locations in northern Egypt: a 'rural ' and a 'suburban' site, from October 2000 and November 2002. The antiozonant ethylenediurea (EDU) and the fungicide chlorothalonil (1,3-benzenedicarbonitrile-2,4,5,6 tetrachloroisophthalnitrile) were applied as a foliar spray to plants at both sites. It was found that foliar injury symptoms were reduced greatly in plants treated with EDU and/or chlorothalonil, and the yield of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…Later studies utilized repeatitive (weekly or biweekly) EDU applications to protect plants against chronic O 3 exposures (Clarke et al 1983Hofstra et al 1983;Bambawale 1986;Heggestad 1988;Brennan et al 1990;Legassicke and Ormrod 1981;Toivonen et al 1982). Additional studies utilized variable dosages of EDU (300-500 ppm) to protect plants from acute and chronic O 3 levels, viz., 300 ppm (Hassan 2006), 400 ppm (Wahid et al 2001;Singh and Agrawal 2009;Singh et al 2009b) and 500 ppm (Agrawal et al 2004. Tiwari et al (2005) and Wang et al (2007) conducted dose-response studies on wheat.…”
Section: Application Dose Of Edumentioning
confidence: 96%
See 3 more Smart Citations
“…Later studies utilized repeatitive (weekly or biweekly) EDU applications to protect plants against chronic O 3 exposures (Clarke et al 1983Hofstra et al 1983;Bambawale 1986;Heggestad 1988;Brennan et al 1990;Legassicke and Ormrod 1981;Toivonen et al 1982). Additional studies utilized variable dosages of EDU (300-500 ppm) to protect plants from acute and chronic O 3 levels, viz., 300 ppm (Hassan 2006), 400 ppm (Wahid et al 2001;Singh and Agrawal 2009;Singh et al 2009b) and 500 ppm (Agrawal et al 2004. Tiwari et al (2005) and Wang et al (2007) conducted dose-response studies on wheat.…”
Section: Application Dose Of Edumentioning
confidence: 96%
“…Such information is useful for selecting cultivars to grow in areas that experience high O 3 levels . Yield loss assessments are performed by comparing the yield estimates of EDU-treated and untreated plants in O 3 polluted areas of the USA (Ensing et al 1985;Smith et al 1987), Asia (Wahid et al 2001;Agrawal et al 2004Agrawal et al , 2005Tiwari et al 2005;Wang et al 2007;Singh and Agrawal 2009;Singh et al 2010b, c), Africa (Hassan et al 1995;Hassan 2006) and Europe (Ribas and Penuelas 2000;Brunschon-Harti et al 1995a;Pleijel et al 1999). Yield increments after the application of EDU onto O 3 exposed plants have been reported for onion (Wukasch and Hofstra 1977), navy bean (Hofstra et al 1978;Temple and Bisessar 1979;Toivonen et al 1982), tomato (Legassicke and Ormrod 1981), potato (Bisessar 1982;Clarke et al 1990;Hassan 2006), tobacco (Bisessar and Palmer 1984), watermelon (Fieldhouse 1978), peanut (Ensing et al 1985), radish (Kostka-Rick and Manning 1992;Hassan et al 1995), carrot (Tiwari and Agrawal 2010), bush bean (Kostka-Rick and Manning 1993a, c), snap bean (Vandermeiren et al 1995), mungbean Singh et al 2010b), soybean (Wahid et al 2001), wheat (Agrawal et al 2004;Tiwari et al 2005;Wang et al 2007;Singh and Agrawal 2009) and black gram …”
Section: The Role Of Edu In Assessing Yield Lossesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the protective mechanism of EDU is still not fully understood [18]. Some studies [34][35][36] have shown that EDU acts by maintaining a high antioxidant enzyme activity and level during O 3 exposure, but other studies concluded that EDU does not significantly affect the antioxidant content in leaves [24]. It is also unclear whether EDU limits stomatal O 3 uptake by inducing a decrease in the stomatal conductance of treated plants [16,17].…”
Section: Introductionmentioning
confidence: 99%